Frontispiece: An Introduction to the Combustion of Carbon Materials. Issue 54 (27th September 2022) - Picheau, Emmanuel; Amar, Sara; Derré, Alain; Pénicaud, Alain; Hof, Ferdinand
Abstract : Although carbon combustion has a long tradition to be used for energy production, there are still limitations to the complete understanding of the reaction. A brief summary of the history of carbon combustion together with a detailed discussion of its most important aspects is given in the Review article by F. Hof et al (DOI: 10.1002/chem.202200117 ).